1978
DOI: 10.1007/bf00347395
|View full text |Cite
|
Sign up to set email alerts
|

Giant-cell tumour of bone

Abstract: Abstract. The radiological findings in 138 giant-cell tumours in 135 patients, with adequate clinical, radiological, and histological details, were studied. The purpose was to define the characteristic radiographic appearance of giant-cell tumour on presentation and after treatment and to assess whether radiological grading of the tumours was of value in determining prognosis. Most lesions were subarticular in location and eccentric to the long axis of the bone, had an ill-defined margin, and had eroded and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 13 publications
1
22
1
Order By: Relevance
“…This would mean that the histological grade III BGCT with apparent sarcomatous changes must be regarded as malignant and wide resection is a better choice of surgical treatment. As already pointed out by many authors [11,27,28,34], the present results also indicate that the radiographic grading of BGCT proposed by Campanacci et al [6] is of limited and uncertain value in indicating the prognosis. But among 5 BGCT cases of radiographical grade III with expansion of the tumor into the soft tissue, 2 cases showed local recurrence (case 1 and case 4) ( Table 2).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This would mean that the histological grade III BGCT with apparent sarcomatous changes must be regarded as malignant and wide resection is a better choice of surgical treatment. As already pointed out by many authors [11,27,28,34], the present results also indicate that the radiographic grading of BGCT proposed by Campanacci et al [6] is of limited and uncertain value in indicating the prognosis. But among 5 BGCT cases of radiographical grade III with expansion of the tumor into the soft tissue, 2 cases showed local recurrence (case 1 and case 4) ( Table 2).…”
Section: Discussionsupporting
confidence: 76%
“…Williams et al [37] denied the significance of the normal mitotic counts proposed by King [25] and the histological grading by Jaffe et al [21] in evaluating the behavior of BGCT, staining that potentially aggressive or malignant BGCT are not initially distinguishable as such histologically. Campanacci et al [6] used radiographic criteria for grading BGCT, and Tehranzadeh et al [35] appreciated the radiographic grading as critically important in planning the management of this tumor, but many other authors concluded that radiological assessment of BGCT is of limited and uncertain value in indicating prognosis Eli, 27,28,34].…”
mentioning
confidence: 99%
“…This promotes healing of the fracture contrary to the belief that surgery will disseminate the tumor cells into the soft tissues and adjacent joint [26]. Our study had some limitations.…”
Section: Discussionmentioning
confidence: 87%
“…The most common radiological appearance of osteoclastoma in the skull is an expanding and/or lytic neoplasm that may appear to extend into the surrounding soft tissues, dura or sinuses. The rarity of these lesions explains the few numbers of MRI and CT descriptions of skull giant cell tumors 7,11 .…”
Section: Discussionmentioning
confidence: 99%